Screening anti-metastasis drugs by cell adhesion-induced color change in a biochip. Issue 15 (16th June 2021) - Chou, Shih-En; Lee, Kuang-Li; Wei, Pei-Kuen; Cheng, Ji-Yen
Abstract : Cell adhesion process monitored on a commercial scanner for screening/repurposing drugs with anti-metastasis capability. Abstract : Metastasis is a frequent complication of cancer and accounts for more than 60% of patients' mortality. Despite technological advancements, treatment options are still limited. Ion channels participate in the regulation of cell adhesion, whilst the regulation of cell adhesion further controls metastasis formation. However, to develop a new ion channel inhibitor targeting metastasis takes tremendous effort and resources; therefore, drug repurposing is an emerging strategy in oncology. In previous studies, we have developed a metal-based nanoslit surface plasmon resonance (SPR) platform to examine the influence of drugs on the cell adhesion process. In this work, we developed a scanner-based cell adhesion kinetic examination (CAKE) system that is capable of monitoring the cell adhesion process by measuring color changes of SPR biosensors. The system's performance was demonstrated by screening the anti-metastasis ability of compounds from a commercial ion-channel inhibitor library. Out of the 274 compounds from the inhibitor library, zinc pyrithione (ZPT) and terfenadine were demonstrated to influence CL1-5 cell adhesion. The cell responses to the two compounds were then compared with those by traditional cell adhesion assays where similar behavior was observed. Further investigation of the two compounds using wound healing and transwell assays was performed and inhibitions of both cell migration and invasion by the two compounds were also observed. The results indicate that ZPT and terfenadine are potential candidates for anti-metastasis drugs. Our work has demonstrated the label-free drug screening ability of our CAKE system for finding potential drugs for cancer treatment.